PEMANFAATAN WAKAF UNTUK PERKEBUNAN PISANG MENURUT UNDANG-UNDANG NOMOR 41 TAHUN 2004 TENTANG WAKAF (Studi Kasus di Yayasan Nurul Huda Gogor Sumberjo Desa Sumberjo Kecamatan Purwoasri Kabupaten Kediri) - Dzikri Ubaydilah; Muhammad Muhammad (JURNAL ILMIAH NUSANTARA, 2025)
Waqf could be a key apparatus in Islamic lessons to advance societal well-being, both through beneficial means—like income-generating assets—and wasteful forms—such as building mosques or schools. This ponder investigates how Yayasan Nurul Huda Gogor Sumberjo executed beneficial waqf in Sumberjo Town, Kediri Rule, employing a normative-empirical approach. The establishment oversees waqf resources agreeing to Islamic law and Article 43(2) of Law No. 41/2004. One case may be a banana manor built up on 70 square meters of waqf arrive, whose benefits bolster the Baiturrahman Mosque and MI&RA Nurul Huda. The nazhir’s competence plays a vital part in maximizing waqf benefits. Competent administration guarantees feasible utilize of resources for the good thing about mauquf 'alaih (recipients). The establishment applies a collaborative approach established in straightforwardness and responsibility, reflecting dynamic, naturally mindful waqf administration. This illustrates that beneficial waqf not as it were underpins community welfare but moreover adjusts with the goals of Islamic law (maqasid shari'ah), especially in protecting riches, religion, and judgment skills.